Responsibility effects in decision making under risk - Julius Pahlke; Sebastian Strasser; Ferdinand M. Vieider (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
We explore situations in which a decision-maker bears responsibility for somebody else's outcomes as well as for her own. For gains we confirm the intuition that being responsible for somebody else's payoffs increases risk aversion, while in the loss domain we find increased risk seeking. In a second experiment we replicate the finding of increased risk aversion for large probabilities of a gain, while for small probability gains we find an increase of risk seeking under conditions of responsibility. This discredits hypotheses of a cautious shift under responsibility, and indicates an accentuation of the fourfold pattern of risk attitudes usually found for individual choices.
Keywords: D03; D81; 330; risk attitude; prospect theory; social norms; responsibility; other-regarding preferences